2020
DOI: 10.2302/kjm.2019-0005-oa
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Febrile Urinary Tract Infection Caused by Extended-spectrum Beta-lactamase-producing <i>Escherichia Coli</i> in Children

Abstract: The global prevalence of infections caused by extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli has been increasing. In children, ESBL-producing E. coli manifest mostly as febrile urinary tract infections (fUTIs). This study aimed to elucidate the clinical features of fUTI resulting from ESBL-producing E. coli in Japanese patients. The clinical features of children with E. coli-related fUTI were retrospectively examined. These children underwent treatment at the National Hospital Organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…History of surgical procedures did not increase the risk of ESBL-pE infection (OR 2.0; 95%CI: 0.89-4.392; p=0.096). This study confirmed a very high prevalence of ESBL-pE UTI in this hospital (56,4% in 2018 and 62.9% in 2019) compared to other hospitals in other countries which ranged from 9% to 42% [9][10][11][12]. This condition is not very surprising because the antibiotic use in Indonesia is high, with a higher proportion of antibiotic use was without indication [13][14][15], and the thirdgeneration cephalosporines were the most frequently prescribed in most Indonesian hospitals [16].…”
Section: Resultssupporting
confidence: 86%
“…History of surgical procedures did not increase the risk of ESBL-pE infection (OR 2.0; 95%CI: 0.89-4.392; p=0.096). This study confirmed a very high prevalence of ESBL-pE UTI in this hospital (56,4% in 2018 and 62.9% in 2019) compared to other hospitals in other countries which ranged from 9% to 42% [9][10][11][12]. This condition is not very surprising because the antibiotic use in Indonesia is high, with a higher proportion of antibiotic use was without indication [13][14][15], and the thirdgeneration cephalosporines were the most frequently prescribed in most Indonesian hospitals [16].…”
Section: Resultssupporting
confidence: 86%
“…Previously, there have not been any multicenter studies in Japan on the clinical characteristics of pediatric fUTI. Although Japanese pediatricians use data from the United States and Europe as a clinical reference, it was pointed out by a single-center study that Japan may have a different sex ratio and age distribution for fUTI compared to other countries (Ohnishi et al, 2019). This study aimed to address this issue by clarifying the clinical characteristics of fUTI in Japanese children.…”
Section: Introductionmentioning
confidence: 98%
“…11 Urinary tract infections caused by AMR E. coli and skin and soft tissue infections caused by community-acquired methicillinresistant S. aureus are emerging issues in Japanese children. 12,13 Intractable otitis media caused by multidrug resistant Streptococcus pneumoniae and Haemophilus influenzae have also arisen as problems in the clinical setting. 14 In the following sections, we summarize the problems with AMR and the efforts to address them in children in Japan.…”
mentioning
confidence: 99%